(untitled) (Majalah Kedokteran Bandung, 2024)
One pathophysiology of preterm delivery is maternal or fetal hypothalamus-pituitary-adrenal (HPA) axis activation. The HPA axis can be affected by vitamin D, which increases uterine contractions and affects the body’s immune mechanism against bacterial infections. A lower level of vitamin D in pregnant women is suspected to contribute to the incidence of premature conditions. This study aimed to compare the 25-hydroxy-vitamin D3 concentration in preterm parturient with non-preterm parturient, and the correlation between vitamin D level and the incidence of preterm labor. This comparative analytic study used a cross-sectional approach and involved 46 subjects who were divided into case and control groups. This study was conducted in August–September 2017 at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. The Electro-chemiluminescence Immunoassay (ECLIA) method was used to examine the serum 25-hydroxy-vitamin D3 concentration in case and control groups, demonstrating that 25-hydroxy-vitamin D3 concentration in case group (17.26 ng/mL) was significantly (p<0.0001) lower than in control group (24.30 ng/mL). The correlation coefficient between the 25-hydroxy-vitamin D3 and the incidence of preterm labor was -0.837 (p<0.001). Thus, there was a correlation between the 25-hydroxy-Vitamin D3 level and the incidence of preterm labor that vitamin D supplementation in pregnant women must be considered.